Penerapan Laporan Keuangan Berbasis SAK EMKM Pada Usaha Mikro Kecil Dan Menengah (Studi Kasus UMKM Go Laundry Helvetia) - Febriani Nur Rahman; Meiman Kristian Putra Gulo; Indah Lestari; Intan Afriliyani; Riska Franita (CV. ITTC INDONESIA, 2025)
This study analyses the implementation of the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) in micro, small and medium enterprises (MSMEs), with Go Laundry as a case study. The purpose of this study is to evaluate how Go Laundry's MSMEs adapt and implement financial reporting based on SAK EMKM, as well as identify the challenges and benefits gained. In this study, we used a qualitative method. We directly interviewed the owner/manager of Go Laundry and analysed its financial documents. The results show that the of application SAK EMKM can improve the standard of MSME financial statements, provide more relevant and reliable information for decision-making, and facilitate access to external financing. Nevertheless, there are some barriers in the implementation process, such as limited human resources and accounting understanding that still need to be improved. This article concludes that continuous socialisation and mentoring are needed for MSMEs to optimise the benefits of SAK EMKM implementation. Data collection methods in preparing this article include:a) Field Observation b) Interview. The results of this research Go Laundry MSMEs have not implemented financial reports manually, due to limited knowledge about SAK EMKM.